Secondary scintillation yield in pure krypton - Mano, R. D. P. (2022)
The absolute secondary scintillation yield is of paramount importance for modelling dual-phase or high-pressure gas detectors, to be used in contemporary and in future rare event detection experiments. In addition, the search for neutrinoless double electron capture complements the search for neutrinoless double beta decay and has been measured for 124Xe in several Dark Matter and Double Beta decay detectors, operating at present. Krypton presents itself as an interesting candidate for double electron capture detection experiments. We have studied the krypton secondary scintillation yield, at room temperature, as a function of electric field in the gas scintillation gap. A large area avalanche photodiode has been used to allow the simultaneous detection of the scintillation pulses as well as the direct interaction of x-rays, the latter being used as a reference for the calculation of the number of charge carriers produced by the scintillation pulses and, thus, the determination of the number of photons impinging the photodiode. An amplification parameter of 113 photons per kV per drifting electron and a scintillation threshold of 2.7 Td (0.7kVcm−1bar−1at 293K) was obtained, in good agreement with the simulation data reported in the literature. On the other hand, the ionisation threshold in krypton was found to be around 13.5 Td (3.4kVcm−1bar−1), less than what had been obtained by the most recent simulation work-package. The krypton amplification parameter is about 80% and 140% of those measured for xenon and argon, respectively.